Frontispiece: Polymer Binders Constructed through Dynamic Noncovalent Bonds for High‐Capacity Silicon‐Based Anodes. Issue 47 (22nd August 2019) - Pan, Yiyang; Gao, Shilun; Sun, Feiyuan; Yang, Huabin; Cao, Peng‐Fei
Abstract : With the increasing concerns about global issues such as the greenhouse effect, environmental pollution, and fossil fuel depletion along with the rapid growth of energy storage markets, lithium‐ion batterys (LIBs) with high energy density are playing increasingly important roles in several fields, including portable electronics, transport systems, energy storage grids, and communication devices. In their Review article onpage 10976 ff., Yang and Cao et al. summarize polymer binders constructed through dynamic noncovalent bonds for Si‐based electrodes in LIB applications and discuss recent progress of polymer binders with hydrogen bonding, ionic bonding, host–guest interactions, and multidynamic bonds.